SWATH-MS Analysis of FFPE Tissues Identifies Stathmin as a Potential Marker of Endometrial Cancer in Patients Exposed to Tamoxifen - Janacova, Lucia; Faktor, Jakub; Capkova, Lenka; Paralova, Vendula; Pospisilova, Anna; Podhorec, Jan; Ebhardt, Holger Alexander; Hrstka, Roman; Nenutil, Rudolf; Aebersold, Ruedi; Bouchal, Pavel (Journal of proteome research, 2020)
A specific form of endometrial cancer (EC) can develop in breast cancer patients previously treated with tamoxifen (ET), an antagonist of estrogen receptor (ER) that inhibits proliferation of ER positive breast cancer. ET tumors have a different phenotype than endometrial tumors, which typically develop de novo without previous exposure to tamoxifen (EN). Here we aimed to identify specific protein markers that could serve as specific molecular targets in either phenotype. A set of total 45 formalin-fixed paraffin-embedded (FFPE) endometrial tumor tissues and adjacent myometrium tissue samples were analyzed using LC-MS/MS in SWATH-MS mode. We found that calcyphosin (CAPS) levels were elevated in EN tumors compared to ET tumors. The higher CAPS level in EC tissue invading to myometrium supports its relationship to EC aggressiveness. Further, stathmin (STMN1) levels were found significantly elevated in ET versus EN tumors and significantly associated with patient survival. This finding connects elevated levels of this cell cycle regulating, proliferation-associated protein with tamoxifen exposure. In summary, using SWATH-MS we show that CAPS and STMN1 should be recognized as clinicopathologically different EC markers of which STMN1 is specifically connected with a previous tamoxifen exposition.
Keywords: nádory endometria; nádory prsu; Endometrial Neoplasms; lidé; Female; Tamoxifen; tandemová hmotnostní spektrometrie; Chromatography, Liquid; stathmin; Breast Neoplasms; Stathmin; tamoxifen; chromatografie kapalinová; ženské pohlaví; Tandem Mass Spectrometry; Humans